PENGOLAHAN BUAH NANAS UPAYA PEMBERDAYAAN USAHA KPH WARGA TRANS DI DESA SUNGAI BESAR KABUPATEN KETAPANG - Saefullah, Aep; As’ad, Ihwana; Maulidiana, Lina; Lidyawati, Anna; Lestari, Lilla Puji; Nurasiah, Nurasiah (LP2M STP Mataram, 2024)
This community service is part of the Team Based Project of the 2021 Independent Campus Young Fighters Program organized by the Ministry of Social Affairs in collaboration with the Ministry of Education and Culture, Research and Technology and the Ministry of Religion of the Republic of Indonesia. The activity was carried out from November 15 to December 11, 2022 to four transmigration community groups consisting of 38 beneficiary families of the Family Hope Program (PKH) Sungai Besar Village, South Matan Hilir District, Ketapang Regency, West Kalimantan Province. The activity organizers consisted of 6 lecturers and 3 students of the Ministry of Social Affairs Merdeka Campus Young Fighters from various universities. The activity method is used by socializing pineapple fruit processing, training on marketing strategies for processed pineapple fruit products, pretest and post test and monitoring evaluation. The results showed that based on community service activities, this activity was significantly beneficial to residents. This program has opened up opportunities for residents to develop skills in processing available natural resources, such as pineapple fruit, into marketable products. The participation of Sungai Besar Village residents in the socialization of pineapple fruit processing is very positive and enthusiasm is high for this business development opportunity. Constraints encountered, (1) variations in participants' educational backgrounds and experiences led to differences in their speed and ability to understand the material. (2) Limited access to resources. (3) Use of technical language and terms in the materials. (4) time availability. (5) Concerns about business sustainability and economic risks were also raised. The 4P (Product, Price, Place Promotion) marketing training provided the importance of developing attractive products, appropriate pricing, efficient distribution strategies, and promotions that reach the target audience. This activity not only improves their ability in the technical aspects of product processing, but also in the business and marketing aspects that will help them earn wages or profits. This program not only provides new skills, but also encourages the economic independence of trans people. They become more productive, can utilize local potential, and contribute to the family and community economy. 4 Indicators of the program's success include the ability of residents, Sungai Besar Village becoming a tourist destination icon for pineapple processed souvenirs, increasing community income and utilization of peatlands into pineapple cultivation land